2011
DOI: 10.1309/ajcp2sd8rfqeuzjw
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of the Diagnostic Accuracy of Frozen Section for Parotid Gland Lesions

Abstract: We conducted a systematic literature review using MEDLINE and Embase to identify articles on diagnostic accuracy of frozen section (FS) for salivary gland lesions published between January 1, 1985, and December 31, 2010. We also reviewed the reference lists of all identified articles and conducted a forward search using Scopus to identify all articles citing the reference set. Meta-analysis was used to produce a summary receiver operating characteristic (SROC) curve from which summary estimates of sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 27 publications
1
61
2
2
Order By: Relevance
“…Although Schmidt et al [8] recommend that one should accept malignant FNA diagnoses and not benign FNAs, our data suggest the opposite. We concur that the specificity of FNA is high and that we have relatively few false positives; however, at our center, we were able to detect these false positives on FS.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Although Schmidt et al [8] recommend that one should accept malignant FNA diagnoses and not benign FNAs, our data suggest the opposite. We concur that the specificity of FNA is high and that we have relatively few false positives; however, at our center, we were able to detect these false positives on FS.…”
Section: Discussioncontrasting
confidence: 85%
“…The meta-analysis reported that a malignant diagnosis by FNA is acceptable, whereas benign diagnoses may be unreliable due to a false-negative rate of 20% for FNA [5]. In a subsequent systematic review and meta-analysis, Schmidt et al [8] found FS of parotid lesions to have a diagnostic accuracy of 99%, a specificity of 99%, and a sensitivity of 90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is frozen and examined immediately and results can then be telephoned to the surgeon within 2030 min. This is useful where no preoperative diagnosis [29] . IOFS mandates a full SEB and so cannot be reco mmended as a firstline diagnostic technique, parti cularly as patients cannot be consented appropriately.…”
Section: Intra-operative Frozen Sectionmentioning
confidence: 99%
“…The 9-tier system has an overall sensitivity of 61%, specificity of 97%, positive predictive value of 82%, and negative predictive value of 91% for the diagnosis of malignancy. A systematic review and meta-analysis 17 on the diagnostic accuracy of FNA for parotid gland malignancies reported a sensitivity of 80% and a specificity of 97%. The 9-tier system falls short on sensitivity.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%